Representações de língua construídas no discurso de professoras de língua portuguesa - Maran, Nilmara Milena Gomes (Universidade Federal de Roraima, 2022)
Increasingly, the issue of teacher education assumes importance due to the requirements and demands that are assigned to education in contemporary society. Bearing this in view, reflect on language representations is relevant to understand the discursive ongoing changes in teaching Portuguese. Within this context, this study aims to present and analyze the language representations constructed in the discourse of teachers who teach English language in elementary school II in public schools located in downtown Boa Vista, RR, in order to observe if the language teaching contemplates the linguistic diversities inherent rooms for multicultural classes. From a theoretical point of view, I situate it in Social Discourse Theory, comprising language as a form of social practice, formed by relations of power and invested with ideologies capable of constituting the social dimensions of knowledge, relationships and social identity. These discussions are theoretically relevant, especially when articulated with the theory of Social Representations that talks about the power relations in everyday life, constituting essential elements that interfere in the effectiveness of Portuguese language teaching. To discuss matters of language, I have the collaboration of theorists from different areas in order to sustain the dialogue and exchange of experience among those taking the multiple aspects of the processes and practices in teaching Portuguese as a subject of reflection and / or empirical analysis. In methodological terms, I utilize the Focus Group as a qualitative data collection feature. Thus, I analyzed the speech of teachers seeking to understand the motivating factors for professional choice. Then I analyzed the discourse together with drawings produced by schools teachers, who designed representations of home-school and building-school. These analyzes showed that the relation between representations of constructed language in the discourse of teachers and the social structure of which they are part is dialectical, since the reasons which led them to opt for teaching profession are reflected in the representations of school, which in turn contribute for the construction of the knowledge and belief on Portuguese language, wherein the discursive formation which constitutes the discursive practice of teachers is constitutive in a conventional manner, contributing to reproduce society systems.